On the question of the rules for the development of working projects by the land development regarding the protection of lands from acidification (liming of acid soils) - Koshel, A.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2022)
As a result of intensified agriculture, excessive use of nitrogen fertilizers in the race to increase yields, there is a rapid increase in the acid reaction of soils on part of the arable lands of Ukraine. An increase in soil acidity leads to suppression of microbiological activity in the arable layer of the soil, accumulation of mobile forms of nutrients harmful to plants, damage to plants by diseases, assimilation of radionuclides and heavy metals by plants, accumulation of nitrates in them. Due to suppression of the root system by free aluminum, the winter resistance and drought resistance of grain crops decreases, the weeding of the fields increases (most weeds can withstand the acidic reaction of the soil solution), while acidity has a negative effect on all soil biota. The problem is gaining special importance and requires urgent state intervention. Liming is the most economically available method of improving soil acidity. Lime can be used both to maintain the desired level of soil acidity and to restore the pH to the appropriate level. Deacidification of the soil by only one value (pH from 5.0 to 6.0) contributes to an increase in productivity by up to 50%. In this study, theoretical and methodological approaches to the development of working land management projects for the protection of lands from acidification (liming of acidic soils) are proposed.